2013
DOI: 10.1002/rds.20048
|View full text |Cite
|
Sign up to set email alerts
|

Multitemporal radar backscattering measurement of wheat fields using multifrequency (L, S, C, and X) and full‐polarization

Abstract: [1] This paper presents the measurements of the backscattering coefficients over the wheat fields using an L-, S-, C-, and X-band scatterometer system during a whole period of wheat growth. The wheat field located at Qionglai County of China was measured during a wheat growing season from November 2010 to May 2011. Twelve experimental acquisitions (ground and radar data) were measured over the wheat field in a flat area at VV-, VH-, HV-, and HH-polarizations of L-, S-, C-, and X-bands, with the incidence angle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 14 publications
2
20
0
Order By: Relevance
“…An F-test was used to verify the extraction accuracy. 33,34 The average values of the measured biomass are 0.42 and 4.14 kg∕m 2 , and of the retrieved biomass are 0.39 and 3.74 kg∕m 2 August 5, 2009, in the research, which were lower than the critical value 3.79, so the retrieved parameters were not significantly different from the measured values. …”
Section: Resultsmentioning
confidence: 64%
See 2 more Smart Citations
“…An F-test was used to verify the extraction accuracy. 33,34 The average values of the measured biomass are 0.42 and 4.14 kg∕m 2 , and of the retrieved biomass are 0.39 and 3.74 kg∕m 2 August 5, 2009, in the research, which were lower than the critical value 3.79, so the retrieved parameters were not significantly different from the measured values. …”
Section: Resultsmentioning
confidence: 64%
“…However, the backscattering coefficients on the 145th growth day are smaller than those on the 115th growth day, which demonstrates that the wheat canopy contributed more to the backscatter attenuation. The soil moisture is 30.5% and 27.6% on the 145th and 165th days, respectively, and the values of biomass, LAI, and weight and length of wheat ears increase by 1.06 kg∕m 2 , 0.99, 1.11 kg∕m 2 , and 4.6 cm, respectively. The backscattering coefficients on the 165th day are larger than those on the 145th day, which shows that the backscatter returned directly from the wheat canopy increases because volume scattering dominates the total backscatter.…”
Section: Backscatter At Hh Vv Vh Polarization At Different Periodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We compared the angular dependence b θ of the VV σ 0 backscatter (in dB, 2016 data) to literature values of forests, short vegetation (crops and shrublands) and bare mineral soils at C-band [38], [39], [17], [40], [41], [42], [43]. Two semi-empirical surface scattering models were assessed in terms of their predicted angular characteristics.…”
Section: A Methodsmentioning
confidence: 99%
“…They concluded that this technique was promising for vascular tissue engineering. [113] Additionally, scaffolds for fabrication and/ or regeneration of body organs (such as heart, liver, and kidney) and the nervous system (including the spinal cord and brain) have been developed. [114] Akhavan et al developed rolled graphene oxide foam (GOF) layers as an electrical conductive 3D scaffold for differentiation of human neural stem cells (hNSCs) that are useful in neural tissue engineering.…”
Section: Nanotechnology and Stem Cell Microenvironmentmentioning
confidence: 99%